BELT AND ROAD INITIATIVE (BRI) MELALUI NEW INTERNATIONAL LAND-SEA TRADE CORRIDOR (ILSTC) SEBAGAI IMPLEMENTASI FILSAFAT KONFUSIANISME - Tiffany Xierry Amanda Anggono; Triesanto Romulo Simanjuntak; Novriest Umbu W Nau (Journal of Innovation Research and Knowledge, 2025)
The rise of China through the Belt and Road Initiative (BRI) is a complex phenomenon that presents opportunities for development while also raising geopolitical and security concerns on the international stage. Several countries perceive the BRI as a threat due to China’s potential economic and political dominance, which could shift Western influence. This study employs a constructivist theoretical approach to offer an alternative perspective by examining the BRI through the ILSTC project as China’s effort to achieve a form of hegemony distinct from traditional understandings. The concept of hegemony analyzed here is rooted in Confucian philosophy, which underpins the values and foreign policy of modern China. The findings indicate that China’s hegemony, as reflected in the BRI and ILSTC, is neither aggressive nor threatening but is based on positive Confucian values such as harmony and virtue. In conclusion, China’s hegemonic approach through the BRI represents a strategy that emphasizes cooperation and joint development, and thus should be understood within the context of China’s culture and history